Biology and Management of Mulberry Weed (Fatoua villosa) in Ornamental Crop Production - Chris Marble; Shawn Steed (EDIS)
This 4-page fact sheet discusses the characteristics of mulberry weed (Fatoua villosa) and explains how to control its growth in a nursery environment. Written by Chris Marble and Shawn Steed, and published by the UF Department of Environmental Horticulture, April 2015.